1978
DOI: 10.1016/s0140-6736(78)90700-6
|View full text |Cite
|
Sign up to set email alerts
|

Hla and Congenital Adrenal Hyperplasia Linkage Confirmed

Abstract: neuronal activity in the locus creruleus5-7 and decreased noradrenaline release.8.9 While clonidine and the opiates have similar effects on the locus coeruleus, clonidine appears to exert specific effects through non-opiate, alpha-2 adrenergic receptors. 6, These data suggested that the opiate-withdrawal syndrome is due to increased noradrenergic neuronal activity in areas such as the locus coeruleus which are regulated both by alpha-2 adrenergic and opiate receptors. Our preliminary results in man support a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Dupont et al (1977) have established that this form of CAH is in close linkage with the B locus of the HLA system. These findings have been confirmed by others (Price et al 1978, Weitkamp et al 1978. and it is suggested that there is n o evidence that the genes for the salt-loosing This work was in part supported by a special research grant kindly donated by the Shaklee family, and grants from Misrad Haklita, State of Israel, U S .…”
supporting
confidence: 77%
“…Dupont et al (1977) have established that this form of CAH is in close linkage with the B locus of the HLA system. These findings have been confirmed by others (Price et al 1978, Weitkamp et al 1978. and it is suggested that there is n o evidence that the genes for the salt-loosing This work was in part supported by a special research grant kindly donated by the Shaklee family, and grants from Misrad Haklita, State of Israel, U S .…”
supporting
confidence: 77%
“…Subsequently, this assay has been widely used for prenatal diagnosis in second-trimester amniotic fluid (Forest, 1985;Pang et al, 1985;Couillin and Raux-Demay, 1986). Dupont et al (1977) and other groups (Price et al, 1978;Couillin et al, 1982) have demonstrated that 21 -OH deficiency behaves like an autosomal recessive trait in close linkage with the HLA-B locus. Additional studies of families with intra-HLA recombinant haplotypes suggested that the 2 1-OH deficiency gene is located between HLA-B and HLA-D (Levine et al, 1978).…”
Section: Introductionmentioning
confidence: 92%
“…Family studies have shown that the disorder is linked to the major histocompatibity (HLA) complex on the short arm of chromosome 6 (Dupont et al 1977;Price et al 1978) and a correlation of certain HLA antigens with particular forms of the disorder has been reported, notably that between the normally rare HLA-Bw47 antigen and the salt-wasting form. Subsequent molecular genetic analyses have located the normally functional 21-hydroxylase gene CYP21B and a highly homologous pseudogene CYP21A in the class III region of the HLA complex (White et al 1985;Higashi et al 1986;Rodrigues et al 1987).…”
Section: Introductionmentioning
confidence: 99%